Cellular and molecular cues of glucose sensing in the rat olfactory bulb - Al Koborssy, Dolly; Palouzier-Paulignan, Brigitte; Salem, Rita; Thevenet, Marc; Romestaing, Caroline; Julliard, A. Karyn (Frontiers in Neuroscience, 2014)
In the brain, glucose homeostasis of extracellular fluid is crucial to the point that systems specifically dedicated to glucose sensing are found in areas involved in energy regulation and feeding behavior. Olfaction is a major sensory modality regulating food consumption. Nutritional status in turn modulates olfactory detection. Recently it has been proposed that some olfactory bulb (OB) neurons respond to glucose similarly to hypothalamic neurons. However, the precise molecular cues governing glucose sensing in the OB are largely unknown. To decrypt these molecular mechanisms, we first used immunostaining to demonstrate a strong expression of two neuronal markers of glucose-sensitivity, insulin-dependent glucose transporter type 4 (GLUT4), and sodium glucose co-transporter type 1 (SGLT1) in specific OB layers. We showed that expression and mapping of GLUT4 but not SGLT1 were feeding state-dependent. In order to investigate the impact of metabolic status on the delivery of blood-borne glucose to the OB, we measured extracellular fluid glucose concentration using glucose biosensors simultaneously in the OB and cortex of anesthetized rats. We showed that glucose concentration in the OB is higher than in the cortex, that metabolic steady-state glucose concentration is independent of feeding state in the two brain areas, and that acute changes in glycemic conditions affect bulbar glucose concentration alone. These data provide new evidence of a direct relationship between the OB and peripheral metabolism, and emphasize the importance of glucose for the OB network, providing strong arguments toward establishing the OB as a glucose-sensing organ.